2017
DOI: 10.1186/s12891-017-1768-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between preoperative American Society of Anesthesiologists Physical Status Classification scores and functional recovery following hip-fracture surgery

Abstract: BackgroundLittle is known about the relationship of the American Society of Anesthesiologists Physical Status Classification scores (ASA scores) on patient outcomes following hip fracture surgery in Asian countries. Therefore, this study explored the association of patients’ preoperative ASA scores on trajectories of recovery in physical functioning and health outcomes during the first year following postoperative discharge for older adults with hip-fracture surgery in Taiwan.MethodsThe data for this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
3
19
3
Order By: Relevance
“…In this context, a higher ASA-Score and a higher age were the only predictors for a lower ability to walk in our study population. This is consistent with other studies [13,14,23,32].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this context, a higher ASA-Score and a higher age were the only predictors for a lower ability to walk in our study population. This is consistent with other studies [13,14,23,32].…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with international studies which showed in-hospital mortality rates between 3 and 10% [13,16,2831]. In addition, ASA score has been previously found to have an influence on mortality after a fracture of the hip [14,23,32]. In our cohort, a short time to first mobilization is associated with a lower mortality rate.…”
Section: Discussionsupporting
confidence: 92%
“…Bone condition changes associated with hyperglycemia or chronic renal disease could affect bone quality, delaying bone-ingrowth fixation at the bone-implant interface, the bone healing process, vascularisation, and subsequent mechanical stability 24 . In their study, Chen et al 22 found that a higher ASA score was associated with older patients that had low bone density (79.39 ±7.85 years old). Those results might explain our finding that the ASA score affected femoral stem subsidence.…”
Section: Discussionmentioning
confidence: 93%
“…The comorbidity assessment using ASA scores showed a correlation to various factors, including the length of stay, the severity of complications, and the treatment's total cost. A higher ASA score was associated with a higher risk of post-operative complications and mortality rates 15 , 22 . This study showed a significant relationship between ASA score 3 with the stem subsidence (p = 0.011, OR = 2.77).…”
Section: Discussionmentioning
confidence: 94%
“…The pain intensity level was evaluated by Numerical Rating Scale (NRS) values. The prediction of the operative risk has been evaluated by American Society of Anaesthesiologists (ASA) physical status classification [10].…”
Section: Methodsmentioning
confidence: 99%